Pengaruh Role Ambiguity Dan Burnout Terhadap Kinerja Auditor Internal - Mira Oktapia Lisa; Justinia Castellani (Jurnal Riset Mahasiswa, 2023)
This study aims to determine the effect of role ambiguity and burnout on performance of internal auditors at the internal auditors of PT. Telekomunikasi Indonesia Tbk. The research approach used in this research is descriptive analysis and verification using primary data. The population in this study are auditors who work at PT. Telekomunikasi Indonesia Tbk. and the number of samples taken as many as 30 auditors. The sampling technique used is non-probability sampling with saturated sampling technique. Statistical analysis used in this study is multiple linear regression, correlation and coefficient of determination. While the hypothesis testing used is the statistical method of t and F tests. Based on the results of the research conducted, it can be seen that the role ambiguity partially has a significant negative effect on the performance of the internal auditor by 62.2%. The burnout variable partially has a significant negative effect on the performance of internal auditors by 21.7%. The variables of role ambiguity and burnout simultaneously have a significant negative effect on the performance of internal auditors by 83.9%, meaning that the lower the role ambiguity and burnout of the internal auditors, the better the performance of internal auditors will be.